Postoperative Nausea and Vomiting in Patients Undergoing Total Abdominal Hysterectomy Under Subarachnoid Block: A Randomized Study of Dexamethasone Prophylaxis - Khatiwada, S; Bhattarai, B; Biswas, BK; Pokharel, K; Acharya, R; Singh, SN; Uprety, D (Kathmandu University Medical Journal, 2013)
Background Postoperative nausea and vomiting is a common distressing problem in patients undergoing gynaecological surgery under anaesthesia including central neuraxial blockade, which requires frequent medical interventions. Objectives We aimed to find out the antiemetic effect of prophylactic dexamethasone for prevention of postoperative nausea and vomiting in patients undergoing total abdominal hysterectomy under subarachnoid block. Influences of dexamethasone on patient satisfaction and postoperative analgesia were also observed as secondary objectives. Methods This was a prospective, randomized, double blind, placebo controlled study conducted in BPKIHS, a Tertiary care University based hospital from January 2009 to April 2009, for a period of four months. This study involved 80 American Society of Anaesthesiologist Physical Status I&II patients undergoing total abdominal hysterectomy under subarachnoid block. Patients were divided into two groups of 40 each to receive either 4 mg of dexamethasone (group D) or normal saline (group N) in volume of 2 ml intravenously 1 hourr prior to subarachnoid block. Surgery was allowed to start with block height of at least T8 dermatome. Intraoperative and postoperative nausea and vomiting was observed using nausea and vomiting scale every 4 hour for 24 hours. Results Seven (17.4%) patients in group D and 11 (27.5%) patients in group N had nausea and vomiting in the intraoperative period (P=0.284). Sixteen (40%) patients in group D experienced nausea and vomiting in the postoperative period as compared to 27 (67.5%) in group N (P =0.0136). Accordingly, the mean requirement of rescue antiemetic was less in group D compared to Group N (P=0.042). Further, only 15 (37.5%) patients in group D required postoperative supplemental analgesic as compared to 23 (57.5%) in group N (P=0.058). After 24 hrs of surgery, 26 (65%) patients expressed satisfaction in group D as compared to 16 (40.0%) in group N (P =0.025). Conclusions Use of dexamethasone prior to subarachnoid block in patients undergoing total abdominal hysterectomy significantly reduces the incidence of nausea and vomiting and the requirement of antiemetic in the postoperative period, with better patient satisfaction. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 41-45 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7342